The Implementation of Guidelines for Cleaning, Health, Safety, and Environmental Sustainability of Homestay/Tourism’s Pondok in Pandanrejo Village, Purwekorto, Central Java - Ratih Pitria Purnamasari; Nenden Dianawati; Ita Maemunah; Dody Affandi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of tourist villages is one of the efforts to grow local entrepreneurial potential, diversify tourism products, support the local community's economy, and revitalize local culture. One of the tourist villages that can be developed into a tourist destination is Pandanrejo Village, Purworejo, Central Java.Pandanrejo is one of the tourist villages that is included in the top 50 best tourist villages in Indonesia which is assessed by the Ministry of Tourism and Creative Economy. To support the sustainability of tourist villages, this research was carried out as a measuring tool as a reference for control in the application of health protocol standards Cleanliness, Health, Safety and Environmental Sustainability (CHSE) to prevent the spread of the COVID-19 outbreak, especially in Homestays located in Pandanrejo Tourism Village, Purworejo Regency, Central Java. This health protocol standard refers to the bookGuidelines for the Implementation of Hygiene, Health and Environmental Sustainability Homestay / Pondok Wisata issued and published by the Ministry of Tourism and Creative Economy. This guidebook is intended for the tourism industry in preparing products and services that are clean, healthy, safe, and environmentally friendly during the Covid-19 pandemic. The research method used is a survey method for the application of general and specific guidelines according to the CHSE health protocol. The research team also used interview and observation methods to obtain the necessary.